2005
DOI: 10.1007/s10267-005-0240-1
|View full text |Cite
|
Sign up to set email alerts
|

The stimulation of extracellular carbohydrases of edible mushrooms by the hot water-soluble fraction from corn fiber

Abstract: Corn fiber (CNF) is an abundant by-product of the wet corn milling process in the production of cornstarch. We have shown that the hot water-soluble fraction (HWSF) from CNF has a promoting effect on the mycelial growth of various edible mushrooms, including mycorrhizal fungi. To reveal the promoting mechanisms, the effect of CNF-HWSF on the stimulation of extracellular enzymes was examined. The production of extracellular carbohydrases such as amylase, CMCase, and xylanase was markedly enhanced by the additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…The supplementation of the tested substrates with wheat bran and soybean flour increased N pool and readily available carbohydrates level, stimulating so initial endoglucanase and biomass production (Silva et al 2005a, Arai et al 2005. The deceleration of growth rate after the 3rd week of colonization, being in agreement with previous results (Leatham 1985), indicates the limitation of utilizable nutrients and soluble carbon sources (Mata and Savoie 1998).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The supplementation of the tested substrates with wheat bran and soybean flour increased N pool and readily available carbohydrates level, stimulating so initial endoglucanase and biomass production (Silva et al 2005a, Arai et al 2005. The deceleration of growth rate after the 3rd week of colonization, being in agreement with previous results (Leatham 1985), indicates the limitation of utilizable nutrients and soluble carbon sources (Mata and Savoie 1998).…”
Section: Discussionsupporting
confidence: 87%
“…This is further supported by the positive correlation of biomass and endoglucanase production found in the present study, as the higher endoglucanase level could be due to higher biomass production. Arai et al (2005) demonstrated that exocarbohydrase and particularly xylanase production correlate with growth promotion of L. edodes mycelium.…”
Section: Discussionmentioning
confidence: 98%